PENGARUH ECO-EFFICIENCY TERHADAP NILAI PERUSAHAAN DENGAN LEVERAGE DAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Novensya Dwi Panggau; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to analyze the effect of eco-efficiency on firm value by leverage and profitability as a moderating variable. Eco-efficiency as an independen variable is measured by dummy. Firm value as dependen variable is measured by market price. Leverage and profitability as moderating variable, leverage is measured by DER and profitability is measured by ROA. This research uses price book value and earnings per share as a control variable. The sample of this research is manufacturing companies listed in Indonesia Stock Exchange during the period 2013 – 2015. The sampling method in this research is purposive sampling. The analysis technique in this study using multiple linear regression analysis. The result show that eco-efficiency has significant positive effects on the firm value. Leverage has positive effects but can’t moderates the relationship between eco-efficiency and firm value. Profitability has negative effects and can’t moderates the relationship between eco-efficiency and firm value.